Pemanfaatan Smartphone dan Digital Marketing 4.0 Dalam Meningkatkan Penjualan di Masa Pandemi Covid-19 Berdasarkan Teori Difusi Inovasi - Patra Anggana, Reza (Koaliansi : Cooperative Journal, 2024)
Abstract This study aims to obtain an overview of the use of smartphones in implementing marketing 4.0 based on the diffusion of innovation theory. The conclusion from the results of this study is that MSMEs show that the use of smartphones in digital marketing 4.0 and supported by the theory of diffusion of innovation, both through diffusion of centralisation and diffusion of decentralisation, really helps them in interacting both directly and indirectly with consumers with an easier and cheaper transaction process because they only spend internet costs to support communication. This research is a descriptive qualitative type here explaining a problem formulation which then guides research to explore or portray the social situation to be studied thoroughly, broadly and deeply. The data used is secondary data by collecting data in the form of electronic documents that explain the facts accessed online. With smartphones, MSMEs get huge benefits compared to conventional methods, because they can reduce the amount of costs and time spent in the sales process as well as expand market share and increase sales turnover.